Duplikátory nerezových tlakových aparátů - Kamarád, Miroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Tlakové nádoby zaujímají významné místo na poli procesních zařízení díky jejich širokému využití v různých odvětvích průmyslu. Z pohledu návrhu a dimenzování je kladen velký důraz na přesnost, spolehlivost a především bezpečnost. Bakalářská práce je zaměřena na zhotovení pevnostní analýzy tlakového duplikátoru dle normy ČSN EN 13 445 [1]. Pevnostní analýza byla provedena metodou konečných prvků (MKP) s využitím programu ANSYS Workbench společně s kategorizací napětí dle ČSN EN 13 445 [1].

Pressure vessels occupy a prominent place in the field of process equipment due to their wide use in various industries. From design and dimensional point of view, great emphasis is placed on accuracy, reliability and above all safety. The bachelor thesis is focused on the stress analysis of the jacketed pressure vessel according to ČSN EN 13445 [1]. The stress analysis was performed with use od finite element method (FEM) using ANSYS Workbench software together with stress categorization by EN 13445 [1].
Jacketed stainless steel pressure Vessel
Keywords: Tlaková nádoba; duplikátor; pevnostní analýza; kategorizace napětí; MKP; ANSYS Workbench; Pressure vessel; Jacketed pressure vessel; stress analysis; stress categorization; FEM; ANSYS Workbench